EFFECTS OF SUNSET POLICY PROGRAM TO THE FACTORS THAT INVOLVE THE WILLINGNESS TO PAY TAX (A RESEARCH ON PERSONAL BUSSINESSMAN AS TAX OBJECT IN WEST SEMARANG DISTRICT REGION) (Students' Journal of Accounting and Banking, 2012)
This research is intended to test the effect of Sunset Policy program to the consciousness of people’s tax paying, deep knowledge of tax regulation and good perception of tax system’s efectiveness. This policy is issued in hope to rise citizen’s willingness to pay tax.This research used primary data gathered by giving questioner to 51 responden who are bussinessman tax object listed in Industry and Mercandhising Department of Semarang City in the region of West Semarang District, using Systematic Random Sample. This research made use of Simple Linier Regretion to analize datas.The yields of this research showed that Sunset Policy have a positif effect to the consciousness of people’s tax paying, deep knowledge of tax regulation and good perception of tax system’s efectiveness.Keywords: Sunset Policy, consciousness to pay tax, deep knowledge of tax regulation, good perception of tax system’s efectiveness.